Stegodexamene anguillae (Digenea: Lepocreadiidae), an intestinal parasite of eels (Anguilla spp.) in New Caledonia - Moravec, F; Justine, J-L (Parasitology research, 2007)
Adult trematodes of the genus Stegodexamene Macfarlane, 1951 were recorded from the intestines of two species of freshwater eels, the Pacific short-finned eel Anguilla obscura Günther and the speckled longfin eel Anguilla reinhardtii Steindachner from the Pouembout and La Foa Rivers, New Caledonia, South Pacific. They were identified as Stegodexamene anguillae Macfarlane, 1951, a species previously reported only from eels in New Zealand. The morphology of adult S. anguillae seems to be practically identical with that of the later described Stegodexamene callista Watson 1984 from eels in Australia. The finding of S. anguillae in A. obscura and A. reinhardtii in New Caledonia represents new geographical and host records. In addition to this trematode, two larval specimens of a cestode of the order Proteocephalidea were found in the intestine of one A. obscura from the Pouembout River. No monogenean was found in eels of New Caledonia.
Keywords: Trematoda; Nová Kaledonie; Larva; New Caledonia; nemoci ryb; Anguilla; Animals; Trematode Infections; Fish Diseases; infekce červy třídy Trematoda; Gastrointestinal Tract; zvířata; gastrointestinální trakt; Cestoda; larva